2020
DOI: 10.3762/bjnano.11.93
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth regulation by seed coating with films of alginate and auxin-intercalated layered double hydroxides

Abstract: Auxins are a class of organic substances known as plant-growth regulators, which act on plant physiology, promoting its full development. However, due to the great instability of these substances among the diversity of crops and cultivation environments, it is necessary to seek more efficient modes of application, which lead to a homogeneous distribution and promote a sustained release according to the plants demand. Seed coating, using films containing a biodegradable polymer and auxins intercalated into laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…To promote the growth of plant tissue culture materials, we need to find a more efficient application model to ensure an even distribution of plant growth regulators in plant tissues. At the same time, we also need to supply plant growth regulators according to the needs of the plant tissue to achieve the rapid accumulation of plant tissue biomass [ 117 ]. Nano-carriers have great prospects for the application of plant growth regulators such as layered double hydroxide (LDH) [ 15 ] and chitosan nanoparticles [ 16 ].…”
Section: Application Of Technology With Different Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…To promote the growth of plant tissue culture materials, we need to find a more efficient application model to ensure an even distribution of plant growth regulators in plant tissues. At the same time, we also need to supply plant growth regulators according to the needs of the plant tissue to achieve the rapid accumulation of plant tissue biomass [ 117 ]. Nano-carriers have great prospects for the application of plant growth regulators such as layered double hydroxide (LDH) [ 15 ] and chitosan nanoparticles [ 16 ].…”
Section: Application Of Technology With Different Fieldsmentioning
confidence: 99%
“…Yanfang Liu et al [ 123 ] used the ion exchange method to insert sodium naphthalene acetate (NAA, a plant growth regulator) into layered double hydroxide Mg/Al-LDH, so that NAA showed a significant release effect. Vander A. de Castro et al [ 117 ] used an alginate polymer (a substance with good biodegradability) to encapsulate zinc-aluminum LDH and NAA to act on plant seeds. The results showed that the alginate film containing ZnAl–NAA–LDH enhanced the root area, fresh root material, and shoot length of the plants.…”
Section: Application Of Technology With Different Fieldsmentioning
confidence: 99%
“…4k and l). 71 Although the intercalation of the auxins within the LDH can facilitate their slow release and reduce the amount of AI required, the inhibited germination of coated seeds can be a drawback due to potential reduction in crop yield. Recently researchers have also explored the use of quaternary ammonium alginate salts as seed coatings.…”
Section: Recent Approachesmentioning
confidence: 99%
“…7,8 The use of polymeric membranes in the coating of bean seeds (Phaseolus vulgaris L.), from organic-inorganic hybrid materials, incorporating 1-naphthaleneacetic acid (NAA), is an example of how these materials have shown good results in the physiological characteristics of the plant, improving its development. 9 Another example has been the use of organicinorganic hybrid materials in the coating of sugarcane microstalks, to reduce the percentage of stalks used in the crop planting process. 10 From this perspective, this study focused on preparing organic-inorganic hybrid materials to coat garlic bulbils as a preplanting treatment.…”
Section: Introductionmentioning
confidence: 99%